EFFECT OF VEGETATION AND BUILDING DENSITIES TO URBAN THERMAL COMFORT (CASE STUDY OF DENPASAR CITY) - Hamim Zaky Hadibasyir; Nada Salsabila Firdaus (Department of Environmental Engineering-Faculty of Civil, Planning, and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2022)
Denpasar is the capital of Bali Province, which is one of the most popular tourist destination in Indonesia. Anthropogenic activities have changed the land use and land cover (LULC) that affect the land surface temperature (LST) and thermal comfort. Good quality of thermal comfort can improve the livelihood of its citizen as well as the tourists. This research aims a) to analyses the density distribution of vegetation and buildings, b) to map the distribution of LST and thermal comfort, and c) to analyses the effect of vegetation and building density on thermal comfort in Denpasar City. LST and thermal comfort were extracted using Landsat 9. Thermal comfort was assessed using urban thermal field variance index (UTFVI). Then, Pearson correlation and simple regression were applied to investigate the relationship and effect of Effect of vegetation and building densities to urban thermal comfort. In general, high density of vegetation is located in the northern part of North Denpasar District, north and east of East Denpasar District, and south of South Denpasar District. High density buildings are scattered in the southern Denpasar District, the western eastern Denpasar District, the northern South Denpasar District, and parts of the West Denpasar District. Low UTFVI values indicate good thermal comfort. Greater vegetation and lower building densities are likely to have an impact by improving thermal comfort levels in a location. This research can be served as a guidance in urban heat island mitigation as well as ecological restoration planning.